Safety and efficacy of a new outreach distal access catheter, TACTICS, for coil embolization of unruptured intracranial aneurysms. Issue 5 (October 2018) - Matsushige, Toshinori; Sakamoto, Shigeyuki; Ishii, Daizo; Shinagawa, Katsuhiro; Shimonaga, Koji; Hosogai, Masahiro; Kawasumi, Tomohiro; Oshita, Junpei; Okazaki, Takahito; Kurisu, Kaoru
Background and purpose: Current large-bore catheters can be easily and safely placed in the intracranial vessels for the stabilization of microcatheters in several neurointervention scenarios. We considered that a novel 3.4 French catheter (TACTICS, Technorat Corporation, Aichi, Japan) might be useful for intermediate/distal access in a triaxial system. Here, we present our initial experience using the TACTICS catheter for treatment of intracranial aneurysms. Materials and methods: A total of 35 endovascular coils were placed to embolize unruptured intracranial aneurysms of the anterior circulation using the TACTICS catheter between December 2016 and November 2017. These procedures were retrospectively reviewed to assess aneurysmal obliteration (Raymond's classification), the volume embolization ratio (VER) and procedural complications in comparison with 96 conventional coil treatments during the 3-year period up to 2016. Data were matched for aneurysmal morphology (location, maximum diameter and aspect ratio) by the propensity method. Results: In all procedures, the TACTICS catheter was atraumatically landed beyond the carotid siphon. There were no hemorrhagic or symptomatic ischemic complications. After propensity matching, 68 procedures were assessed (34 in each group). Achievement of Raymond's scale 1 (complete occlusion) showed the same frequency in both groups (50% vs. 50%, p = 0.23). The VER was significantly higher with the TACTICS catheter than with the conventional method (34.0% vs. 28.7%, p = 0.003). Conclusion: We reviewed our initial experience of the TACTICS catheter. It can be used as an intermediate catheter for safe and effective endovascular coil embolization of anterior circulation aneurysms.